Private (t,n) threshold searching on streaming data - Yi, Xun (2013)
Private searching on streaming data is a process to dispatch to a public server a program, which searches streaming sources of data without revealing searching criteria and then sends back a buffer containing the findings. From an Abelian group homomorphic encryption, the searching criteria can be constructed by only simple combinations of keywords, e.g., disjunction of keywords. The recent breakthrough in fully homomorphic encryption has allowed us to construct arbitrary searching criteria theoretically. In this paper, we consider a (t, n) threshold query, which searches for documents containing more than t out of n keywords. This form of query can help us find more relevant documents. We present a construction of the searching criteria for private threshold searching on streaming data on the basis of the state-of-the-art fully homomorphic encryption techniques. Our protocol is semantically secure as long as the underlying fully homomorphic encryption scheme is semantically secure.